Effect of Reaction Products on the PEFC Catalyst Ink Property and Catalyst Layer Quality. (8th September 2020) - Uemura, Suguru; Sakai, Katsunori; Sasabe, Takashi; Matsumoto, Hidetoshi; Sugimori, Hidekazu; Shinohara, Kazuhiko; Hirai, Shuichiro
Abstract : The catalyst layer is a critical component of proton exchange membrane fuel cells. Previous studies suggest that several reaction products were generated in the catalyst ink mixing process and it can effect on the structure of the catalyst layer. In this study, by identifying the reaction product contained in the catalyst ink and measuring those quantitative concentration, the effects on the catalyst ink and the catalyst layer were investigated. As a result, it was shown that acetaldehyde can affect the catalyst ink properties and the catalyst layer quality (micro-scale crack formation).